Urease de helicobacter pylori : produção, marcação fluorescente e estudo da biodistribuição por imageamento óptico in vivo - Higuchi, Kiyo Costa (2021)
Alzheimer’s Disease (AD) has the presence of brain neurofibrillary tangles – deposits of the hyperphosphorylated tau protein – among its histopathological hallmarks. AD patients are more often infected with Helicobacter pylori (a gastric pathogen) than healthy individuals, and it has been reported that an H. pylori culture filtrate induced tau hyperphosphorylation in vitro and in vivo. H. pylori infects about half of the world’s population, and its survival in the human stomach is only viable due to the enzyme urease (H. pylori urease, HPU), possibly involved in AD pathogenesis, although little is known about its in vivo biodistribution. The present work aimed to investigate HPU’s absorption and biodistribution kinetics in the nude mouse (Mus musculus Foxn1nu) model using in vivo optical imaging. For this purpose, HPU was produced, characterized, labeled with fluorophores, and given intraperitoneally to the animals. The protein’s oligomerization states were monitored during weeks, and it displayed stability in the dodecameric form. In silico studies indicated the presence of potentially free amino acid residues in HPU’s surface for fluorescent labeling, and the latter did not affect HPU’s enzymatic activity. The developed methodology was efficient in acquiring in vivo images to monitor the biodistribution and absorption and excretion kinetics of the labeled HPU. Rapid absorption of the protein by the circulatory system from the peritoneal cavity and later excretion by the kidneys was observed, followed by the migration to the bladder – approximately 40 min after the injection. Further investigations involving chronic treatment with HPU are required to seek deeper clarification on the mechanisms through which the enzyme, produced by a gastric pathogen, may be involved in neuropathogenic processes.